2020
DOI: 10.1001/jamacardio.2020.3409
|View full text |Cite
|
Sign up to set email alerts
|

Stress Myocardial Perfusion Imaging vs Coronary Computed Tomographic Angiography for Diagnosis of Invasive Vessel-Specific Coronary Physiology

Abstract: IMPORTANCEStress imaging has been the standard for diagnosing functionally significant coronary artery disease. It is unknown whether novel, atherosclerotic plaque measures improve accuracy beyond coronary stenosis for diagnosing invasive fractional flow reserve (FFR) measurement.OBJECTIVE To compare the diagnostic accuracy of comprehensive anatomic (obstructive and nonobstructive atherosclerotic plaque) vs functional imaging measures for estimating vessel-specific FFR.DESIGN, SETTING, AND PARTICIPANTS Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…4,5,7,25,30 These plaque features have been associated with inducible ischemia, identified as precursors for ACS, and independently predict MACE. 5,6,31 Recently, Williams et al reported that a low attenuation plaque burden was associated with a >6-fold increase in incident MI for patients with nonobstructive CAD. 4 Controlled clinical trials reveal that FFR-CT improves diagnostic accuracy over and above obstructive CAD on CCTA when compared with invasive FFR.…”
Section: Evaluation Of Patients With Stable Chest Painmentioning
confidence: 99%
“…4,5,7,25,30 These plaque features have been associated with inducible ischemia, identified as precursors for ACS, and independently predict MACE. 5,6,31 Recently, Williams et al reported that a low attenuation plaque burden was associated with a >6-fold increase in incident MI for patients with nonobstructive CAD. 4 Controlled clinical trials reveal that FFR-CT improves diagnostic accuracy over and above obstructive CAD on CCTA when compared with invasive FFR.…”
Section: Evaluation Of Patients With Stable Chest Painmentioning
confidence: 99%
“…normal or abnormal AI-QCT ischaemia result ( Graphical Abstract ). AI-QCT ischaemia was trained against invasive FFR with cut-off 0.80, 9 , 15 using data from the CREDENCE ( Computed tomogRaphic Evaluation of atherosclerotic DEtermiNants of myocardial isChEmia ) 16 trial (50:50 derivation and internal validation) and has undergone external validation using data from the PACIFIC ( Prospective Comparison of Cardiac PET/CT, SPECT/CT Perfusion Imaging and CT Coronary Angiography With Invasive Coronary Angiography ) 17 trial.…”
Section: Methodsmentioning
confidence: 99%
“…An important answer to this question has been provided by the results of the CREDENCE trial, 22 that demonstrated on a cohort of 612 patients that a comprehensive anatomic interpretation with CCTA (namely the quantification of obstructive and non-obstructive atherosclerotic plaque, percentage of non-calcified atheroma volume, lumen volume, the number of lesions with HRP and the number of lesions with stenosis greater than 30%) was superior to functional imaging in the diagnosis of invasive FFR (AUC 0.81 for CCTA vs. 0.67 respectively, P < 0.001).…”
Section: Functional Ct Analysismentioning
confidence: 99%